Quality of Education, Productivity Changes, and Income Distribution - Mehta, Shailendra Raj (Journal of Labor Economics, 2000)
A general equilibrium model of a dual economy is constructed with workers and managers and hierarchical production. Ability is continuous, and there is perfect competition in the product market. Higher quality of education is treated as a form of technical progress. An equilibrium wage profile is derived. Different kinds of technical and productivity changes yield different gainers and losers. Declines in the quality of education generally lead to an increase in inequality. Surprisingly, groups suffering from declines in quality of education often benefit at the cost of others. Parallels are drawn with recent experience.